Pengaruh Efisiensi Perusahaan, Ukuran Perusahaan, Leverage dan Likuiditas Terhadap Profitabilitas Perusahaan Kesehatan yang Terdaftar di BEI - Putri, Ervina Rahmalia; Fuad, Sofiyul; Sofia, Mega Lailatus; Nurhayati, Citra (JURNAL ADMINISTRASI KANTOR; Vol 11 No 1 (2023): Jurnal Administrasi Kantor (Juni 2023)DO - 10.51211/jak.v11i1.2310, 2023)
This study aims to analyze the effect of company efficiency, company size, leverage and liabilities on the profitability of healthcare companies listed on the Indonesia Stock Exchange during the 2018-2021 period. The number of manufacturing companies used as research samples is 21 companies for 4 years. This research is based on purposive sampling technique. The total sample of this research is 84 financial statement observations. Testing the hypothesis using multiple linear regression tests through the IBM SPSS 25 program. The partial results show that company efficiency has a significant positive effect on profitability, firm size has no effect on profitability, leverage has a significant effect on profitability with a negative direction, and liquidity has no effect on profitability. The results of the study simultaneously show that efficiency, company size, leverage, and liquidity simultaneously affect the profitability of health sector companies listed on the Indonesia Stock Exchange (IDX).   Keywords: Company Efficiency, Leverage, Profitability, Company Size.